The Effect of Inquiry Model and Cognitive Style on Understanding of The Concept of Integrated IPS Course Students of Unila History Education Program - Imanita, Myristica; Ekwandari, Yustina Sri; Arif, Suparman (Journal of Research in Social Science and Humanities, 2021)
IPS Terpadu is a combination of several social sciences, one of which is story, but the students of fkip unila history still have difficulty understanding the concept IPS Terpadu so his study aimed to determine the effect of inquiry instructional model and cognitiveÂ Â  style towards the understanding students concepts in IPS Terpadu subjects. The research is quantitative research using design treatment by level 2x2 The research date was taken from observation,test and questionnaires. The results show that (1) there is differences in the level of understanding of the concepts of students who follow the inquiry instructional model and students who follow the conventional instructional model (2) there is interaction effect between instructional model and cognitive style towards the understanding students concepts in IPS Tepadu subjects (3) the results of understanding the concepts of students in IPS Terpadu subjects who follow inquiri instructional model with Field Independent cognitive style is hinger than students who follow conventional instructional model with field indenpendent cognitive style. (4)the risults of underdtanding students of concepts in IPS Terpadu subjects who follow inquiri instructional model with field dependent cognitive style is lower than students who follow conventional instructional model with field dependent cognitive style